Integrated reinforcement of carbon nanotube fibers for enhancement of their applicability, mechanical and electrical properties - Kim, Jae Won; Cho, Hyun Jun; Kim, Seung Min; Kim, Young-Kwan (Elsevier BV, 2025)
This study presents an integrated strategy combining wet-chemical and dry-mechanical processes to enhance the properties and applicability of commercial directly spun carbon nanotube fiber (CNTF) with a high linear density of similar to 6 tex (g km(-1)). The sequential wet-chemical process is demonstrated for the first time based on the cross-linking of polyethyleneimine (PEI) with pyrogallol (PG). The PEI and PG (PEI@PG) treatment of CNTFs improves their properties, followed by twisting to enhance their density and alignment. These rapid sequential processes can be completed within 1 min, and the twisted PEI@PG CNTFs exhibit enhanced tensile strength, modulus, and electrical conductivity from 27.27 MPa, 0.50 GPa, and 2,685 S cm(-1) to 202.44 MPa, 5.89 GPa, and 4,370 S cm(-1). The twisted PEI@PG CNTF shows an improved gravimetric capacitance from 4.92 to 10.33 Fg-(1). The twisted Au nanoparticle-loaded PEI@PG CNTFs are harnessed as a fibrous catalyst for hydrogenation of 4-nitrophenol with a high activity of 0.054 min(-1) and electrochemical glucose sensors with high sensitivity of 304.06 mA mM(-1) cm(-2), detection limit of 0.166 mu M, and a wide linear range from 0.548 mu M to 8.0 mM, respectively. This strategy offers a simple, rapid, and scalable route to enhance the performance and applicability of CNTFs.